Mitigating Green Oil Deactivation in Acetylene Hydrogenation Using Carbon-Supported Pd Catalysts - Hwang, Seokyoung; Hwang, Young Bean; Hwang, Hyun Wook; Kim, Dansil; Lee, Ji Young; Hwang, Jongkook; Park, Eun Duck; Kim, Seok Ki (Advanced Energy and Sustainability Research, 2024)
This study investigates the mitigation of green oil deactivation in acetylene hydrogenation using carbon-supported Pd catalysts. Various carbon supports including CMK-3, short CMK-3, activated carbon, graphite, mesoporous carbon, graphite nanofiber, and carbon nanotube, are compared. Catalyst performance, including deactivation rates and product selectivity, is evaluated under high acetylene concentration conditions. Comprehensive characterization of catalyst properties is conducted using techniques such as scanning electron microscope, Ar physisorption, X-ray photoelectron spectroscopy, Raman spectroscopy, CO chemisorption, and thermogravimetric analysis. The study reveals that carbon-supported catalysts generally exhibit slower deactivation rates compared to alumina-supported catalysts. Among carbon supports, carbon nanotube demonstrates exceptional stability, while graphite shows rapid deactivation. The catalyst surface area shows the strongest correlation with the deactivation rate, suggesting that the larger the surface area, the easier it is for the generated green oil to escape without covering the active Pd sites. These findings highlight the importance of textural properties in designing stable catalysts for acetylene hydrogenation and emphasize the need for a holistic approach to catalyst design.
Keywords: Acetylene hydrogenation; Carbon support; Carbon-supported Pd; Deactivation rate; Green oil; Heterogeneous pd catalyst; Mesoporous carbon; Pd catalyst; Supported Pd catalysts; Surface area; acetylene hydrogenation; carbon supports; ethylene; green oil; heterogeneous Pd catalysts